Normalisasi Dalam Perancangan Basis Data Relasional Purchase Order (PO) - Didik Setiyadi (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2018)
Abstrak: Basis data merupakan koleksi terpadu dari data yang saling terintegrasi dengan tujuan untuk kecepatan dalam pengambilan kembali data untuk memenuhi kebutuhan end user suatu perusahaan. Dalam melakukan perancangan basis data dapat dilakukan dengan menggunakan 2 (dua) pendekatan yaitu dengan melakukan normalisasi atau dengan konsep ERD (Entity Relationship Diagram). Normalisasi merupakan teknik formal yang digunakan dalam perancangan basis data untuk menghasilkan rancangan basis data yang optimal yang bebas anomali (insert, update dan delete). Dalam perancangan basis data dengan normalisasi menggunakan kasus data Purchase Order (PO). Dalam normalisasi dilakukan dengan melakukan Unnormalized Form (UNF), First Normal Form (1 NF), Second Normal Form (2NF), Thirt Normal Form (3NF) sampai terbentuknya ERD (Entity Relationship Diagram) dan terbentuknya perancangan struktur tabel dari tabel-tabel yang terbentuk dari hasil normalisasi. Kata Kunci: Anomali, Entity Relationship Diagram, Normalisasi. Abstract: A database is an integrated collection of data are integrated with the purpose to speed in taking back the data to meet the needs of the end user of a company. When doing database design can be done by using 2 (two) approach is to perform normalization or with the concept of an ERD (Entity Relationship Diagram). Normalization is a formal technique used in designing the database to produce an optimal database design that is free of anomalies (insert, update, and delete). In the design of data base with normalization using case data Purchase Order (PO). In the normalization is performed by doing the Unnormalized Form (EXTRACT), the First Normal Form (1 NF), Second Normal Form (2NF), Thirt Normal Form (3NF) until the formation of the ERD (Entity Relationship Diagrams) and the formation of table structure design tables of results of normalization. Keywords: Anomalies, Entity Relationship Diagram, Normalization.